A nanoscale vacuum-tube diode triggered by few-cycle laser pulses - Higuchi, Takuya; Maisenbacher, Lothar; Liehl, Andreas; Dombi, Peter; Hommelhoff, Peter (Applied Physics Letters, 2015)
We propose and demonstrate a nanoscale vacuum-tube diode triggered by few-cycle near-infrared laser pulses. It represents an ultrafast electronic device based on light fields, exploiting near-field optical enhancement at surfaces of two metal nanotips. The sharper of the two tips displays a stronger field-enhancement, resulting in larger photoemission yields at its surface. One laser pulse with a peak intensity of 4.7 × 1011W/cm2 triggers photoemission of ∼16 electrons from the sharper cathode tip, while emission from the blunter anode tip is suppressed by 19 dB to ∼0.2 electrons per pulse. Thus, the laser-triggered current between two tips exhibit a rectifying behavior, in analogy to classical vacuum-tube diodes. According to the kinetic energy of the emitted electrons and the distance between the tips, the total operation time of this laser-triggered nanoscale diode is estimated to be below 1 ps.
UnivIS-Import:2015-04-14:Pub.2015.nat.dphy.IAP.exphys.ananos